Impact of COVID-19 lockdown on sleep quality of pharmacy students in UiTM Puncak Alam - Mizaton Hazizul Hasan; Gamal AE Moustafa (Elsevier, 2022)
Due to the COVID-19 pandemic, the closure of educational institutions was executed during the period of lockdown. This subsequently led to alterations in daily routines and emotional distress, particularly among university students, affecting their sleep quality resulting in disturbance of immune functioning and mood regulation. Hence, the present study aimed to measure students' sleep quality during the first few months of the lockdown period. This study is a cross-sectional, single-centred survey that was done by distributed electronic questionnaire. The e-questionnaire was divided into 4 sections that assessed socio-demographic characteristics, sleep quality, psychological state and engagement in physical activity. Exactly 248 valid responses were received, 82 % female students. Students with poor sleep quality were three times greater than those with good sleep quality. No association were found between physical activity and sleep quality. However, a significant positive relationship between sleep quality and psychological state was observed (p < 0.01). In conclusion, this study suggests that the majority of pharmacy students in UiTM Puncak Alam are poor sleepers and psychological distress negatively affects sleep quality but, is mainly due to stress. Thus, interventions such as stress management programs and mental health support can be taken by the faculty's management to overcome this problem.